2021
DOI: 10.1177/23742895211057239
|View full text |Cite
|
Sign up to set email alerts
|

Educational Case: Burn Injury—Pathophysiology, Classification, and Treatment

Abstract: The following fictional case is intended as a learning tool within the Pathology Competencies for Medical Education (PCME), a set of national standards for teaching pathology. These are divided into three basic competencies: Disease Mechanisms and Processes, Organ System Pathology, and Diagnostic Medicine and Therapeutic Pathology. For additional information, and a full list of learning objectives for all three competencies, see http://journals.sagepub.com/doi/10.1177/2374289517715040 .1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…Luka bakar dapat disebabkan oleh panas atau trauma akut lainnya, seperti listrik, bahan kimia, gesekan, atau radiasi [4]. Perbedaan penyebab luka bakar dapat dikaitkan dengan respon fisiologis dan patofisiologis serta menentukan pendekatan terapi pengobatan yang dilakukan.…”
Section: Hasil Dan Pembahasanunclassified
“…Luka bakar dapat disebabkan oleh panas atau trauma akut lainnya, seperti listrik, bahan kimia, gesekan, atau radiasi [4]. Perbedaan penyebab luka bakar dapat dikaitkan dengan respon fisiologis dan patofisiologis serta menentukan pendekatan terapi pengobatan yang dilakukan.…”
Section: Hasil Dan Pembahasanunclassified
“…Burns encompass a range of intensity of injury determined by the profundity of the maim and the quantity or percentage of the burn of the whole body [22]. Burn has been categorized as superficial (first degree), partial thickness (second degree), and total thickness (third degree), involving just the epidermal layer of the skin, damaging to deeper structures within the skin, and all layers of the skin, respectively [23][24][25]. It has been reported that burns have the possibility to damage structures beneath the skin and deeper tissues.…”
Section: Categories Of Burnmentioning
confidence: 99%
“…In the third-degree burns (full-thickness) as the most serious type, the injury will exceed beyond the dermis layer and reach into the hypodermis 2 . The wound healing process consists of several critical steps comprising hemostasis, inflammation, proliferation and wound remodeling 3 , 4 . The mechanisms underlying the mentioned steps are as follows: (i) growth factors and inflammatory mediators; (ii) cell–cell and cell–extracellular matrix interactions that govern cell migration, proliferation, and differentiation; (iii) events involved with epithelialization, fibroplasia and angiogenesis; (iv) wound contraction; and (v) remodeling 5 .…”
Section: Introductionmentioning
confidence: 99%